Employment Protection and Business Cycles in Emerging Economies - Lama, Ruy (IMF Working Papers; Working Paper, 2011)
We build a small open economy, real business cycle model with labor market frictions to evaluate the role of employment protection in shaping business cycles in emerging economies. The model features matching frictions and an endogenous selection effect by which inefficient jobs are destroyed in recessions. In a quantitative version of the model calibrated to the Mexican economy we find that reducing separation costs to a level consistent with developed economies would reduce output volatility by 15 percent. We also use the model to analyze the Mexican crisis episode of 2008 and conclude that an economy with lower separation costs would have experienced a smaller drop in output and in measured total factor productivity with no significant change in aggregate employment.